2021
DOI: 10.1126/sciadv.abg9998
|View full text |Cite
|
Sign up to set email alerts
|

Climate models generally underrepresent the warming by Central Africa biomass-burning aerosols over the Southeast Atlantic

Abstract: The radiative budget, cloud properties, and precipitation over tropical Africa are influenced by solar absorption by biomass-burning aerosols (BBA) from Central Africa. Recent field campaigns, reinforced by new remote-sensing and aerosol climatology datasets, have highlighted the absorbing nature of the elevated BBA layers over the South-East Atlantic (SEA), indicating that the absorption could be stronger than previously thought. We show that most of the latest generation of general circulation models (GCMs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 79 publications
(138 reference statements)
2
29
0
Order By: Relevance
“…Southern Africa produces approximately one-third of the world's carbon emissions through biomass-burning (van der Werf et al, 2010), with the global majority of the absorbing aerosols above cloud occurring above the southeast Atlantic (Waquet et al, 2013), indicating the importance of realistic representations for this radiative climate (Mallet et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Southern Africa produces approximately one-third of the world's carbon emissions through biomass-burning (van der Werf et al, 2010), with the global majority of the absorbing aerosols above cloud occurring above the southeast Atlantic (Waquet et al, 2013), indicating the importance of realistic representations for this radiative climate (Mallet et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While climate models discern an ensemble-mean direct radiative warming, individual models disagree strongly on magnitude and even sign (Myhre et al, 2013;Zuidema et al, 2016b;Haywood et al, 2021;Mallet et al, 2021). In addition, the direct aerosol radiative effect estimated from satellites typically exceeds model estimates (de Graaf et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the frequently used variables to define model representation for BBA is aerosol optical depth (AOD) which depends on both aerosol abundance and optical properties in the atmosphere. Previous studies have reported that global models produced substantial underestimations of AOD over BB regions with highly varying extent despite using different emission inventories (Kaiser et al, 2012;Veira et al, 2015;Johnson et al, 2016;Reddington et al, 2016;Mallet et al, 2021). For example, Kaiser et al (2012) showed the global Monitoring Atmospheric Composition and Change (MACC) aerosol model driven by emissions from the Global Fire Assimilation System (GFAS) underestimated AOD by a factor of 2-4 for BBA.…”
Section: Introductionmentioning
confidence: 99%